Adaptive geometric control of quadrotors with dynamic offset between center of gravity and geometric center. Issue 4 (25th March 2020) - Sharma, Manmohan; Kar, Indrani
Abstract: A geometric adaptive control of quadrotors has been proposed in this paper when the center of gravity of the quadrotor is different from its geometric center. The unique feature of the controller is the use of left tracking error function to simplify controller design. The inertia matrix, mass as well as the center of gravity are assumed to be unknown and coordinate invariant adaptive laws have been derived for the estimate of these mentioned parameters. The coordinate invariant approach is another unique feature of the proposed method as opposed to the literature. Rigorous mathematical proofs have been prescribed to show the stability of the complete closed loop dynamics under the proposed adaptive laws. The controller has been derived under the assumption that the rotational dynamics is faster than the translational dynamics. Numerical simulations have been shown at the end to show the effectiveness of the proposed method.